Auditoría financiera y su incidencia en los resultados económicos de la empresa imdco c.a, cantón Quevedo, período 2012 - Pisco Benites, Ángela Verónica (2015)
The present investigation was carried out in the company IMDCO C.A, the same one that is located in the canton Quevedo, in the Av. June Guzman of Cortez N° 514 and Tenth Primer; the general objective of investigation consists in: To develop a financial audit in connection with the economic performance of the company IMDCO C.A, canton Quevedo, year 2012.; like part of the investigative process was appealed to the use of the inductive, deductive and descriptive methods, on the other hand, the type der investigation was: exploratory and bibliographical, the same ones that allowed to structure the investigation in a technical way and practice in their group. As a result it was obtained that: the Questionnaire of applied Internal check evidenced some weaknesses of operative character that it maintains the entity; a level of Risk of Control of 12% was obtained, according to the chart it is a level of LOW risk and the obtained Confidence level is of 88% according to the HIGH chart; The financial reasons allow to evaluate the financial information that manages and they present the companies before the regulatory agencies, in the analysis you could evidence in some reasons financial percentages in a level below the normal value. The final result of the audit consists on presenting the critical points of the company and the execution or not of the countable and financial regulatory scheme, therefore the discoveries presented in the report of Internal check, will help the directives of the entity to correct situations that affect to the operations of the entity, since the countable entity maintains weaknesses that interfere in the good administrative and financial acting of the company.